Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00415-016-8126-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for migraine: a systematic review

Abstract: Migraine causes major health impairment and disability. Psychological interventions offer an addition to pharmacotherapy but they are not currently recommended by the National Institute of Clinical Excellence (NICE) or available in the National Health Service. We aimed to systematically review evidence on the efficacy of psychological interventions for migraine in adults. A search was done of MEDLINE, psychINFO, http://www.opengrey.eu, the meta-register of controlled trials and bibliographies. Twenty-four pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 42 publications
1
54
0
2
Order By: Relevance
“…17 Reviews of behavioral treatment have focused on different measures derived from headache diaries (eg, composite indices based on averaging pain ratings that therefore reflect headache frequency, duration, and intensity, vs headache frequency/days), but have all used headache diaries for their dependent variables. 18,19 Presumably, a major reason for this situation, was that for many years, there was no obvious alternative to paper-based diaries for frequent recording of pain ratings. This situation changed with the advent of hand-held computers and smartphones.…”
mentioning
confidence: 99%
“…17 Reviews of behavioral treatment have focused on different measures derived from headache diaries (eg, composite indices based on averaging pain ratings that therefore reflect headache frequency, duration, and intensity, vs headache frequency/days), but have all used headache diaries for their dependent variables. 18,19 Presumably, a major reason for this situation, was that for many years, there was no obvious alternative to paper-based diaries for frequent recording of pain ratings. This situation changed with the advent of hand-held computers and smartphones.…”
mentioning
confidence: 99%
“…Therefore, a comprehensive approach to solving this problem is very important, and education, to both the general population and the patients, and the raising of health care to a higher level, with ongoing support for patients suffering from a migraine, are indispensable for the formation of a healthier society. Combination of pharmacologic and behavioral treatments such as relaxation training and cognitive behavior therapy can lead to faster and better results with people who suffer from migraine [43,44]. Empirically validated behavioral treatments include biofeedback training; relaxation training, combinations of the two, stress management training, and cognitive behavioral therapy could be helpful for people with migraine headache.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has previously reviewed the evidence from trials of complex interventions for headache and found generally positive results. 29 Given scarce resources, it is also crucial to assess cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%